2013
DOI: 10.1074/mcp.m112.021873
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Proteomic and Transcriptomic Approach Shows Diverging Molecular Mechanisms in Thoracic Aortic Aneurysm Development in Patients with Tricuspid- And Bicuspid Aortic Valve

Abstract: Thoracic aortic aneurysm is a pathological local dilatation of the aorta, potentially leading to aortic rupture or dissection. The disease is a common complication of patients with bicuspid aortic valve, a congenital disorder present in 1-2% of the population. Using two dimensional fluorescence difference gel electrophoresis proteomics followed by mRNA expression, and alternative splicing analysis of the identified proteins, differences in dilated and nondilated aorta tissues between 44 patients with bicuspid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 88 publications
4
47
0
Order By: Relevance
“…In the present study, the comparison between proteins released from BAV and TAV aneurysmatic tissues showed diverging expression fingerprints in the two groups of patients. Our results are in agreement with previous findings by Kjellqvist et al [8] that collectively demonstrated that ATAA formation in patients with BAV has clearly diverging expression fingerprints compared with the patients with TAV, at all three levels of gene, exon, and protein analysis. By secretome analysis, we found that BAV aneurysms highlighted 7 proteins down-regulated and 31 up-regulated and, interestingly, 21 out of 38 differentially modulated proteins were involved in TGF-b activation confirming the crucial role of this signaling in ATAA development, especially when associated to bicuspid valve.…”
Section: Discussionsupporting
confidence: 96%
See 1 more Smart Citation
“…In the present study, the comparison between proteins released from BAV and TAV aneurysmatic tissues showed diverging expression fingerprints in the two groups of patients. Our results are in agreement with previous findings by Kjellqvist et al [8] that collectively demonstrated that ATAA formation in patients with BAV has clearly diverging expression fingerprints compared with the patients with TAV, at all three levels of gene, exon, and protein analysis. By secretome analysis, we found that BAV aneurysms highlighted 7 proteins down-regulated and 31 up-regulated and, interestingly, 21 out of 38 differentially modulated proteins were involved in TGF-b activation confirming the crucial role of this signaling in ATAA development, especially when associated to bicuspid valve.…”
Section: Discussionsupporting
confidence: 96%
“…Hypothesis-free proteomics approaches may be useful to elucidate the molecular mechanisms involved in aneurysm formation as well as to identify novel potential markers of pathology severity for early diagnosis or targets of therapy because a change in protein expression may be predictive for the structure and functionality of a tissue. Previous studies have focused on the association of certain genes and proteins with aneurysm by using genomics and proteomics approaches [6][7][8]. The secretome analysis by highthroughput proteomics has been demonstrated to have a great advantage because, mimicking the in vivo secretion mechanism, it shows traces of tissue-specific biological events although implying a reduced complexity compared to the whole tissue proteomics and thus allowing the detection of under-represented potential biomarkers [9].…”
mentioning
confidence: 99%
“…Limited studies of non-inherited diseases have also found few overlapping changes between the two assays [41-43]. Despite this discordance, the annotation analysis of the changes implicated many of the same pathologic processes, with about a third of the functional annotation terms from the two assays being the same.…”
Section: Discussionmentioning
confidence: 99%
“…154 In contrast to the TAV aortic aneurysms, BAV aneurysms were associated with a relative lack of inflammation, normal MMP9 levels, and elevated MMP2 expression. [155][156][157] Because the latter is an activator of TGF-β signaling, 158 this provides indirect evidence of the involvement of TGF-β dysregulation in the pathogenesis of BAV/TAA.…”
Section: Bav-associated Taa: Polygenic or Complexmentioning
confidence: 99%